2018
DOI: 10.1152/ajpheart.00155.2018
|View full text |Cite
|
Sign up to set email alerts
|

Humanin analog enhances the protective effect of dexrazoxane against doxorubicin-induced cardiotoxicity

Abstract: The chemotherapeutic effect of doxorubicin (Dox) is limited by cumulative dose-dependent cardiotoxicity in cancer survivors. Dexrazoxane (DRZ) is approved to prevent Dox-induced cardiotoxicity. Humanin and its synthetic analog HNG have a cytoprotective effect on the heart. To investigate the cardioprotective efficacy of HNG alone or in combination with DRZ against Dox-induced cardiotoxicity, 80 adult male mice were randomly divided into 8 groups to receive the following treatments via intraperitoneal injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 49 publications
(57 reference statements)
2
15
0
Order By: Relevance
“…SN co-supplementation elicited a protective effect by preventing the induction of myocardial fibrosis. The increase in fibrotic tissue prevalence in the heart is a consistent hallmark of DOX-induced cardiotoxicity [52][53][54][55][56] , and our data demonstrate this precedes DOX-induced myocardial toxicity. Surprisingly, SN co-supplementation increased left ventricular wall thickness compared to both the VEH and DOX control group.…”
Section: Discussionsupporting
confidence: 70%
“…SN co-supplementation elicited a protective effect by preventing the induction of myocardial fibrosis. The increase in fibrotic tissue prevalence in the heart is a consistent hallmark of DOX-induced cardiotoxicity [52][53][54][55][56] , and our data demonstrate this precedes DOX-induced myocardial toxicity. Surprisingly, SN co-supplementation increased left ventricular wall thickness compared to both the VEH and DOX control group.…”
Section: Discussionsupporting
confidence: 70%
“…To investigate the therapeutic effect of irisin, mice were subcutaneously infused with either saline or irisin (12 nmol/kg/ day) for 14 days from the 6th day before DOX injection via osmotic minipumps (Alzet model 2004, Alza Corp) as previously described [29,30]. In addition, mice were intraperitoneally injected with a weekly dose of 60 mg/kg DEX for two times, with the first injection at the 6th day before DOX injection, and the second one at the second day after DOX treatment [31].…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…All these mice were observed daily and the survival rate was calculated every week. To compare the effect of irisin and DEX in chronic model, mice with irisin protection were pretreated with irisin (12 nmol/kg/day) for 6 days and lasting for another 6 weeks, whereas mice with DEX administration were intraperitoneally injected with a weekly dose of 60 mg/kg DEX for seven times [29][30][31]. Considering the fact that long-term use of high-doses of DEX resulted in severe side effects, we then investigated whether combined use of DEX with irisin (6 nmol/kg/day) could decrease the usage of DEX.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Several drug families, mainly chemotherapeutics, while having a desired cytotoxic effect responsible for the anti-cancer efficacy, can cause apoptosis, necrosis or both [ 67 , 68 , 69 ]. For example, anthracyclines represented by doxorubicin cause cardiomyocyte loss by inducing apoptosis, demonstrated in cultured cardiomyocytes including iPSC-CMs and experimental animals such as mice and rats [ 62 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Several groups showed that doxorubicin-induced apoptosis is mediated by the generation of reactive oxygen species (ROS) [ 75 , 76 , 83 , 84 ].…”
Section: Drug Development Adverse Drug Reactions Mechanisms Of Cmentioning
confidence: 99%